An examination of students' perceptions of their interprofessional placements in residential aged care. Issue 2 (4th March 2017) - Seaman, Karla; Saunders, Rosemary; Williams, Elly; Harrup-Gregory, Jane; Loffler, Helen; Lake, Fiona
ABSTRACT: It is essential that health professionals are trained to provide optimal care for our ageing population. Key to this is a positive attitude to older adults along with the ability to work in teams and provide interprofessional care. There is limited evidence on the impact an interprofessional education (IPE) placement in a residential aged care facility (RACF) has on students. In 2015 in Western Australia, 51 students (30% male, median age 23 years), from seven professions, undertook a placement between 2 and 13 weeks in length at 1 RACF. Pre- and post-placement measurements of attitudes to the elderly were collected using the Ageing Semantic Differential (ASD) questionnaire and level of readiness for interprofessional learning with the Readiness for Interprofessional Learning Scale (RIPLS). A total of 47 students completed matched ASD and RIPLS surveys. The mean total score on the ASD survey decreased significantly from pre- to post-placement from 116.0 to 108.9 ( p  = 0.033), indicating attitudes became increasingly positive towards older adults. Significant differences post-placement were seen indicating better readiness for interprofessional learning, for two out of four subscales on the RIPLS, namely "teamwork & collaboration" (42.1–44.0; ( p  = 0.000)) and "positive professional identity" (18.2–19.3 ( p  = 0.001)). The degree of change is similar to findings from other settings. The results support IPE-focussed student placements within RACF positively influence student's attitudes towards the older adult as well as increase student's readiness for interprofessional learning, confirming RACF are valuable places for training health professionals.